Knowledge grid model in facilitating knowledge sharing among big data community: systematic literature review - Hossenioun, Sara; Abdullah, Rusli; Jusoh, Yusmadi Yah; A. Jabar, Marzanah (Asian Research Publication Network, 2018)
This systematic literature review (SLR) aimed to identify issues of knowledge sharing in big data community as a huge amount of data and highlight the knowledge grid’s characteristics which can improve knowledge flow between members of a community. In achieving the objectives, this study follows Kitchenham’s, (2009) method for SLR. In consequence, three research questions have been chosen in the first phase and in following phases all the related article which help to answer the research questions by the keywords that have been collected. Analysis of results revealed the difficulty of knowledge sharing between community members’ interaction and collaboration and there is a gap in researches on big data user’s roles on sharing through the big data community. Moreover, knowledge grid as communication infrastructure can effectively acquire, represents and exchanges massive amount of knowledge however current knowledge grid models focus on knowledge discovery through big data and there is a lack of efficient knowledge grid model for distributing knowledge among community members by considering their influence on knowledge.